Mengenal Dinosaurus Dengan Memanfaatkan Game Edukasi Museum Virtual - Agung Bardansyah Hasibuan; Siti Sundari (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
The importance of introducing knowledge about dinosaurs as part of prehistoric life history to children from an early age cannot be overlooked. This understanding equips them with a foundational perspective on Earth's evolution and ancient biodiversity. Unfortunately, conventional teaching methods often fail to capture children's interest, appearing monotonous and lacking immersive learning experiences. This limits their potential to deeply explore and appreciate the wonders of the prehistoric world. Recognizing these limitations, an innovative study was conducted to develop an educational game based on multimedia technology, specifically designed to address these challenges. The primary objective of this game is to enable users—especially children—to learn about various types of dinosaurs through a first-person perspective within a detailed and interactive virtual museum environment. The development method used in this project is the Multimedia Development Life Cycle (MDLC), a systematic framework consisting of six essential stages: concept, design, material collection, creation, testing, and distribution. The game is carefully designed to allow users to explore the museum interactively, as if they were physically present. Users are free to interact with realistic 3D models of dinosaurs and receive educational information through easily understandable visual and audio formats. Test results show that the game successfully provides an enjoyable learning experience, significantly enhances children's interest in dinosaur history, and supports a more interactive and effective learning process. Therefore, this innovative media is expected to serve as a fresh and effective alternative for delivering educational content based on history and science to children, opening doors to deeper understanding and excitement in learning. The game also demonstrated increased learning interest, with 93.8% of users providing positive feedback.